Chemical Compound Characterizations of Patchouli Leaf Extract via GC-MS, LC-QTOF-MS, FTIR, and 1H NMR - Sundarajan, Sangeethavani; Nour, A. H. (ESRSA Publications Pvt. Ltd., 2019)
The demand for patchouli (Pogostemon cablin) essential oil is increasing globally due to its diverse importance in the nutraceutical and pharmaceutical industries. The oil from this plant is an embodiment of different varieties of chemical compounds. It is then important to identify the bioactive compounds in the extracted oil to identify the embedded potential uses of the oil. Hence, this study focused on the characterization of extracted patchouli oil through microwave- assisted hydrodistillation (MAHD) technique using gas chromatography-mass spectrometry (GC-MS), liquid chromatography-mass spectrometry quadrupole time of flight (LC-Q-TOF-MS), nuclear magnetic resonance (NMR), and Fourier transform infrared transmission (FTIR). The obtained results reflected that patchouli leaf oil is endowed with appreciable quantities of non-oxygenated and oxygenated compounds (from GC-MS analysis); 18 tentatively identified phenolic compounds from LC-Q-TOF-MS analysis; several peaks showing the presence of O-H stretching in alcohol, C=O stretching vibration of carbonyl aldehyde, C-H bending stretching of alkane, and C=C stretching from aromatic rings were identified from the FTIR analysis. Additionally, the NMR results reflected the abundance of patchouli alcohol in the oil which can contribute to its aroma. Thus, patchouli leaf oil is an important plant endowed with different bioactive compounds.